Low-Complexity Propagator Based Two Dimensional Angle Estimation for Coprime MIMO Radar - Jianfeng Li; Defu Jiang (IEEE Access, 2018)
The problem of 2-D angle estimation for coprime multiple-input multiple-output (MIMO) radar is considered, and a low-complexity propagator based method is proposed. Coprime MIMO radar is configured with transmit and receive rectangular arrays, where transmit array has N×Q elements while receive array has M×P elements (M is coprime to N while P is coprime to Q). Based on the uniformities of the arrays, unitary transformation is exploited to transform the complex data into real-valued one, and then the signal subspace is obtained from a low-complexity propagator matrix, which requires neither eigenvalue decomposition nor pseudo inversion. Thereafter, automatically paired two pairs of coprime parameter estimations can be acquired based on the rotational invariance within the signal subspace. Finally, unique 2-D angle can be estimated from the coincide result of the coprime estimations. Due to the real-valued propagator based method, the proposed method has low complexity, but it can achieve better angle estimation results than conventional methods. Theoretical analysis of the method is derived, and simulation results are presented to verify the effectiveness of the proposed approach.